PENGARUH PEMAKAIAN KB IUD TERHADAP TERJADINYA POLYMENORRHEA PADA WANITA USIA SUBUR - Sulami Sulami; Nabhani Nabhani (KOSALA : Jurnal Ilmu Kesehatan, 2016)
AbstractPolymenorrhea is a hormonal disorder by the age of the corpus luteum shortenedso that the menstrual cycle becomes shorter. IUD (Intra Uterine Device) or is atool made of smooth plastic metal usually copper or copper salts made in variousforms. How it works is as follows when IUD is located in the womb there was achange in indometrium resulting in damage (lysis) of spermatozoa that canfertilize the ovum. This procedure will affect the menstrual cycle of woman whichis called polymenorrhea.This study aimed to determine the effect of the use of IUD on the incidence ofpolymenorrhea in women of childbearing age.This type of research isanalytic, research with cross sectional approach. Results:The results of the study showed that IUD users as many as 18 people (60%),while the womans who do not used IUD or have history of using IUD as many as12 peoples (40%). IUD users who experienced polymenorrhea were 4 peoples(13.3%) It can be concluded that there was no influence between the use of IUDwith the incidence polymenorrhea. The respondents with a significance level usedis 95% then the critical limit of 0.05, while the result p = 0.079.Keywords: IUD, polymenorrhea, Women of childbearing age.